Educating the Internet-of-Things Generation - Kortuem, G.; Bandara, A. K.; Smith, N.; Richards, M.; Petre, M. (Computer (Long Beach, Calif.), 2013)
The Open University's My Digital Life course offers a learning infrastructure that allows complete novices to experiment with, and learn about, Internet-of-Things technologies by engaging in a range of activities that include collaborative and collective programming of real-world sensing applications. The first Web extra at http://youtu.be/JUpkHqivXp4 is a video presentation in which Arosha Bandara, a lecturer in computing at the Open University, explains how embedded, interconnected devices have grown to affect our lives. The second Web extra at http://youtu.be/VL37sjj_I1sis a video demonstration of Sense from the Open University's My Digital Life course. Sense is a newly developed visual programming language and programming environment based on SenseBoard, an embedded networked sensor device that supports active learning and experimentation with sensing, actuation, and networking by students at home.